Interpersonal Skills of Raja Vegan UMKM HR in Building Relationships - Syafitri, Elvina Nadia; Oktaviana, Rina; Misnawati, Desy; Maharani, Dwi (Indonesian Journal of Advanced Research, 2024)
Interpersonal skills are important skills in developing human resources (HR), especially in the context of Micro, Small and Medium Enterprises (MSMEs). Raja Vegan, an MSME that operates in the field of animal-free, plant-based vegetarian products, understands that building good relationships with various parties is the key to business success. Therefore, this service activity aims to help the development of MSMEs by forming a special institution consisting of lecturers and communication science students from Bina Darma University who continuously dedicate themselves to MSMEs to develop and manage HR skills in establishing good relationships with customers and other related parties and helping MSMEs to further optimize marketing on social media. Improving interpersonal HR skills can be an effective strategy in increasing the competitiveness and sustainability of MSMEs in an increasingly competitive market. Therefore, developing interpersonal skills needs to be a focus in managing the human resources of Raja Vegan MSMEs to achieve long-term success.